2013
DOI: 10.1039/c3cc41039k
|View full text |Cite
|
Sign up to set email alerts
|

Highly propylene-selective supported zeolite-imidazolate framework (ZIF-8) membranes synthesized by rapid microwave-assisted seeding and secondary growth

Abstract: Here we report a rapid and simple microwave-assisted seeding technique for the synthesis of high-quality ZIF-8 membranes with an average propylene-propane selectivity of about 40. The new seeding method was found to be applicable to other ZIFs including ZIF-7 and SIM-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
149
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(155 citation statements)
references
References 34 publications
5
149
1
Order By: Relevance
“…So far, secondary growth (Kwon and Jeong, 2013a;Liu et al, 2014a;Pan et al, 2012) and contra-diffusion (counter-diffusion) methods (Brown et al, 2014;Hara et al, 2014;Kwona and Jeong, 2015) were reported to successfully prepare high-quality ZIF-8 membranes for effective separation of propylene/propane mixtures. However, the reproducibility of these synthesis procedures was limited by some key unmanageable synthesis steps.…”
Section: Introductionmentioning
confidence: 99%
“…So far, secondary growth (Kwon and Jeong, 2013a;Liu et al, 2014a;Pan et al, 2012) and contra-diffusion (counter-diffusion) methods (Brown et al, 2014;Hara et al, 2014;Kwona and Jeong, 2015) were reported to successfully prepare high-quality ZIF-8 membranes for effective separation of propylene/propane mixtures. However, the reproducibility of these synthesis procedures was limited by some key unmanageable synthesis steps.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], titania [23,42], YSC [43], ZnO [44], and SiO 2 [45]. Titania is 173 a substrate that promotes heterogeneous nucleation; however, it is 174 too expensive and brittle [25].…”
Section: Q2mentioning
confidence: 99%
“…Few reports discuss about the importance of 353 reproducibility and methods to achieve it. For an example, rapid 354 microwave-assisted seeding and secondary growth methodology 355 reportedly yielded reproducible ZIF-8 membrane microstructure 356 and separation performance [39]. Modification of substrates with 357 APTES that functions as a covalent linker also reportedly produced 358 reproducible ZIF membrane properties and performance 359 [49,50].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Pan et al first reported the effective separation of propylene/propane with ZIF-8 membranes using the secondary growth method, achieving a selectivity of up to 50 for an equimolar mixture of propylene/propane 22) . Subsequently, Kwon and Jeong 15) and Liu et al 18) also reported ZIF-8 membranes with a comparable propylene/propane separation performance. Recently, the counter diffusion approach, which allows for preparation of ZIF-8 selective layers with fewer defects via a simple protocol, has gained prominence.…”
Section: Introductionmentioning
confidence: 97%